ARTISTIC INTERPRETATION OF THE FOLK EPIC "ALPOMISH" ON THE STAGE OF THE SYRDARYA REGIONAL MUSICAL DRAMA THEATER (International journal of artificial intelligence, 2026)
This article is devoted to the analysis of the play "Alpomish" staged by the Syrdarya Regional Musical Drama Theater. Based on the text fragments from the sources, the main themes of the play, such as loyalty, expectation and the struggle for justice, are considered. Special attention is paid to the place of folklore elements, in particular, ritual songs in the dramatic action.